2022
DOI: 10.3389/fgene.2022.1041524
|View full text |Cite
|
Sign up to set email alerts
|

Construction of artificial neural network diagnostic model and analysis of immune infiltration for periodontitis

Abstract: Background: Periodontitis is a chronic inflammatory disease leading to tooth loss in severe cases, and early diagnosis is essential for periodontitis prevention. This study aimed to construct a diagnostic model for periodontitis using a random forest algorithm and an artificial neural network (ANN).Methods: Gene expression data of two large cohorts of patients with periodontitis, GSE10334 and GSE16134, were downloaded from the Gene Expression Omnibus database. We screened for differentially expressed genes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…However, very little is known about the role of the other 5 identified genes in CD at present. It is reported that the expression levels of RGS13 in colon tissues associate with endoscopic remission after vedolizumab in IBD patients ( 45 ). FOLH1 can increase folic acid levels, which may promote proliferation of inflammatory cells ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, very little is known about the role of the other 5 identified genes in CD at present. It is reported that the expression levels of RGS13 in colon tissues associate with endoscopic remission after vedolizumab in IBD patients ( 45 ). FOLH1 can increase folic acid levels, which may promote proliferation of inflammatory cells ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, on how to construct a low-dimensional diagnostic model based on high-dimensional data that still performs stably in the validation set remains a research challenge. The key benefits of random forest (RF) are its accuracy and resistance to overfitting, which makes it a good choice of machine learning algorithms (Wu et al, 2022), and it has also shown consistent diagnostic efficacy in previous studies (Sun et al, 2022;Wu et al, 2022;Xiang et al, 2022).…”
Section: Introductionmentioning
confidence: 90%
“…Gini coe cient method was used to calculate the dimensional signi cance value for screening the important genes as the candidate genes for IFTA diagnosis. The IFTA candidate genes for ANN model development was de ned from the top 15 DEGs with signi cance value greater than 2, which is a acceptable screening index in RF and has been used in similar studies (12,15).…”
Section: Random Forest Screeningmentioning
confidence: 99%
“…The key bene ts of Random Forest (RF) are its accuracy and resistance to over tting, which makes it a good choices of machine learning algorithms (12). The use of Arti cial Neural Networks (ANNs) allows for the creation of nonlinear models, and make it is possible to detect nonlinear relationships and all potential interactions among predictor variables (13).It has been reported that RF and ANN can be used in conjunction to make e cient diagnoses in a wide range of diseases, such as Alzheimer"s disease, heart failure and periodontitis (12,14,15).…”
Section: Introductionmentioning
confidence: 99%